The Influence of the Implementation of SIMDA Finance, Competence and Training on Employee Performance at the Surakarta DPRD Secretariat - Irwanto Irwanto; Siti Nurlaela; Agni Astungkara (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Performance is the process of someone's behavior to create something that is the goal of his work. Performance can be affected by a number of factors, including the implementation of SIMDA finance, competence and training. This study aims to determine the effect of implementing SIMDA finance, competence and training on employee performance. This research is quantitative. The number of samples is 60 employees at the Surakarta DPRD Secretariat who were selected using saturated sampling. Multiple linear regression analysis was used as a data analysis technique. This research is indicated by the results of t arithmetic > t table (2,638 > 2.003) and sig. of 0.011 <0.05, meaning that it accepts H1, meaning that the implementation of financial SIMDA has an effect on employee performance. So that there is a significant influence between the implementation of financial SIMDA on the performance of the Surakarta DPRD secretariat employees, which is proven to be true. The results of the calculation of the value of t arithmetic > t table (5.259 > 2.003) and sig. of 0.000 <0.05, meaning that it accepts H2, namely competence has an effect on employee performance. So that there is a significant influence between competence on the performance of the Surakarta DPRD secretariat employees, which is proven to be true. The calculation value of t count > t table (3.517 > 2.003) and sig. of 0, < 0.05, it means accepting H3, that is, training has an effect on employee performance. So that there is a significant influence between competence on the performance of the Surakarta DPRD secretariat employees, which is proven to be true. The conclusion of this study is that the application of SIMDA finance, competence, and training has a significant positive effect on employee performance at the Surakarta DPRD secretariat.